Biodegradation of triplochiton scleroxylon K. Schum tectona grandis linn, gmelina arborea roxb, nauclea diderichii linn and terminalia ivorensis A. chev by lenzites palisoti Fr. (2010)
Triplochiton scleroxylon, Tectona grandis, Gmelina arborea, Nauclea diderichii and Teminalia ivorensis wood blocks were biodegraded in situ in the laboratory by Lenzites palisoti a white rot fungus. The test blocks were cut into 10x10x20mm and exposed into the infection region of pure culture of Lenzites palisoti for 16 weeks. The test blocks were examined for weight loss at 4 weeks interval. The percentages of weight loss obtained after 4, 8, 12 and 16 weeks of incubation of the test blocks in Lenzites palisoti indicated that decay occurred at a relatively constant rate. After 16 weeks, micro morphological analysis of the decayed wood showed that the action of the cellulolytic enzymes of Lenzites palisoti was restricted to cell wall surface.